Parteiprogramme Sprachliche Gestalt und Textgebrauch - Ickes, Andreas (Büchner-Verlag, 2008)
Why a study of political language use? The most important tool in politics is language, as an instrument with which opinions are articulated and disseminated, with which political decisions and decisions representing the will of the people are made. However, the language of politics is also a language of influence. Thus, political parties try to promote their own programs with the help of their party programs (basic programs, election programs) and in this respect represent an important as well as interesting type of text in the field of political communication. Party programs serve, for example, to promote internal party understanding, external self-presentation and as a basis for public understanding. Andreas Ickes presents the text type party program in its various variations and forms of realization. He documents those aspects of the linguistic form that are characteristic of this text type and locates the use of de type party program in the structure of political communication. The detailed presentation is underpinned with cross-party sample material, annotated text passages, or even forms of contrastive analysis. Thus, the analysis and reflection of political language use helps not only to recognize the linguistic possibilities of conveying content, but also to improve one's own critical faculties.